2007
DOI: 10.2183/pjab.83.175
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of pierisin-1 activities in the adult cabbage white butterfly, Pieris rapae, during storage after killing

Abstract: Crude extracts from larvae, pupae and adults of cabbage white butterflies, Pieris rapae and Pieris brassicae, and green-veined butterfly, Pieris napi, have an ability to induce apoptosis in the human cancer cell lines. As apoptosis inducing protein, pierisin-1 and -2 have been isolated from pupae of P. rapae and P. brassicae, respectively, and shown to exhibit DNA ADP-ribosylating activity. Although the highest activity was detected in the late phase of larvae and early phase of pupae, certain activity was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Both activities were decreased by Ϸ20% compared with fresh samples (18). In the present study, we found that crude extracts from dried adult samples of Talbotia naganum, Aporia gigantea, Aporia hippia, Delias pasithoe, and Appias nero exhibited cytotoxicity and DNA ADP-ribosylating activity.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Both activities were decreased by Ϸ20% compared with fresh samples (18). In the present study, we found that crude extracts from dried adult samples of Talbotia naganum, Aporia gigantea, Aporia hippia, Delias pasithoe, and Appias nero exhibited cytotoxicity and DNA ADP-ribosylating activity.…”
Section: Discussionsupporting
confidence: 54%
“…Recently, we reported that cytotoxic and DNA ADP-ribosylating activities of pierisin-1 in adults of Pieris rapae persisted to some extent in the body after killing. Both activities decreased to Ϸ20% for 8 weeks (18). This is valuable information in that adult specimens after death can still be used for examination of the presence of substance having pierisin-like activity, at least for a few months, thus increasing the availability of species in this study.…”
mentioning
confidence: 82%
See 3 more Smart Citations